FORMATION OF MORAL AND AESTHETIC STUDENTS 'VALUES BY MEANS OF SONG REPERTURE (Pedagogy of Higher and Secondary Education, 2001)
In this article is considered the opportunities of chorus singing repertoire in developing moral-aesthetical values of pupils. The meaning of value is revealing. The philosophical and psychology-pedagogical literature about moral and aesthetical upbringing connection is analyzed about the emotional-moral influence of art on person. Modern methods to the tasks of music are considered as aesthetical upbringing of schoolchildren, caused by moral aesthetical nature of art-creativity.